2012
DOI: 10.1186/cc11198
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular ejection fraction using an ultrasonic stethoscope in critically ill patients

Abstract: IntroductionAssessment of cardiac function is key in the management of intensive care unit (ICU) patients and frequently relies on the use of standard transthoracic echocardiography (TTE). A commercially available new generation ultrasound system with two-dimensional imaging capability, which has roughly the size of a mobile phone, is adequately suited to extend the physical examination. The primary endpoint of this study was to evaluate the additional value of this new miniaturized device used as an ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…In a perioperative setting, Frederiksen and colleagues [18] confirmed that PUD was well suited for performing a focus-assessed TTE in a surgery setting with a good image quality. More recently, Amiel and colleagues [16] demonstrated that PUD was able to assess LVEF with a good agreement in 94 critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a perioperative setting, Frederiksen and colleagues [18] confirmed that PUD was well suited for performing a focus-assessed TTE in a surgery setting with a good image quality. More recently, Amiel and colleagues [16] demonstrated that PUD was able to assess LVEF with a good agreement in 94 critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its true portability, ease of use, and relative low cost make this device adequately suited for routine use in strategies of focused US examination. At present, only a few studies evaluating its feasibility and clinical usefulness have been published [16-20]. However, none of them has compared its diagnostic accuracy with that of standard echocardiography in emergency settings.…”
Section: Introductionmentioning
confidence: 99%
“…There was a good agreement between both techniques for all items examined. Similar results were obtained in 94 critically ill patients [23]. In that trial left ventricular ejection fraction (LVEF) was independently assessed clinically by the attending physician and echocardiographically by two experienced intensivists trained in critical care echocardiography who used the pocket ultrasound and a fully featured device (CX50, Philips Healthcare, Eindhoven, The Netherlands).…”
Section: Hemodynamic Monitoringmentioning
confidence: 73%
“…(5) Its use has become very common in some medical specialties such as emergency medicine, anesthesia and critical care. Several prior studies have demonstrated validity and reliability (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%